Wydatki wojskowe i obronne na Węgrzech w latach 1949–1979 - Germuska, Pál (Pamięć i Sprawiedliwość, 2010)
The study presents the development of the military and defence expenses during the period of 1949 to 1979, based on so far unknown, formerly top secret sources. It describes the decisional mechanisms, the party and state organisations having the competence to determine the mentioned expense, as well as the international circumstances and internal events influencing the volume of the military expense. From 1949 till 1956 a dual budgetary system was in application in Hungary as well: beside the official, public budget existed a secret budget containing the military expense and state dotations to be dissimulated. Concerning the military expenditure, as from 1956 another hiding technique was also in use: the budget line of the Ministry of Defence contained exclusively the operational costs, while the cost of investments and weapon acquisitions was placed among the items of the national economy investments and the trade expenditure.